The Effect of Mathematical Thinking Ability With Alberta Inquiry Learning Models Towards Discrete Mathematics Learning Outcomes - Heleni, Susda; Zulkarnain, Zulkarnain (Proceedings of the UR International Conference on Educational Sciences, 2018)
Mathematical thinking is a mathematical process, which includes five aspects; mathematical understanding, mathematical communication, mathematical connections, mathematical reasoning and mathematical problem solving. Discrete Mathematics is one of the subjects that can develop students thinking skills. One of the lessons that can be applied to improve students mathematical thinking skills is the Alberta Inquiry learning model. This research aims to discover the effect of mathematical thinking capabilities with the learning model of Alberta Inquiry towards the learning achievement of Discrete Mathematics Study Program FKIP of Universitas Riau in the even semester of 2017/2018 academic year. The form of this research is a quasi-experimental research. The experiment design used in this research is the Single Group Pretest /Posttest design Without Control Group. The sample of this research is students of the 6th semester Mathematics Study Program of Class A in the even semester of 2017/2018 academic year consisting 31 peoples.Based on the considerations of the researchers taken class A as the sample in this research with the reason that students in class A first took Discrete Mathematics courses in the even semester of 2017/2018 academic year. The result of the normality test of pretestand postest showed that the pretest data werenot normally distributed (sig = 0,004 < Î± = 0,05) and the postest data was normally distributed (sig = 0,200 > Î± = 0,05). The results of two similarity test average obtained sig = 0,00< Î± = 0,05 means postest value is better than pretest. The results of testing the determination index coefficient obtained the value of r2xy = 0,52with Kp = 52%. In other words itcan be concluded that there is an effect of mathematical thinking ability with Alberta Inquiry learning models towards Discrete mathematics learning outcomes is 52%.